PENERAPAN EVIDENCE BASED NURSING AROMATERAPI LAVENDER DAN MATERNITY PILLOW TERHADAP KUALITAS TIDUR IBU HAMIL TRIMESTER III DENGAN KELUHAN NYERI PUNGGUNG DI KELURAHAN GROGOL DEPOK - Siska Agustina Lestari, (2023)
Pregnancy is a physiological and natural process in which the union of sperm and egg cells occurs from conception until the baby is born or 9 months of gestation. One form of change that occurs in third trimester pregnant women is sleep pattern disturbance. About 78% of pregnant women experience sleep rhythm disturbances. Sleep disorders in third trimester pregnant women are caused by increased frequency of urination, back pain, fetal movements, hypersalivation. One of the non-pharmacological therapies that can be used to treat sleep pattern disturbances in pregnant women is by using lavender aromatherapy and maternity pillows. The content in lavender flowers functions as a sedative effect so that the aroma produced can improve sleep quality while the use of maternity pillows can also help pregnant women determine a comfortable position during sleep so that they can reduce complaints of back pain during sleep. Objective: to determine the effect of using lavender aromatherapy and maternity pillows on the sleep quality of third trimester pregnant women with complaints of back pain. The method is carried out by giving lavender aromatherapy and maternity pillows 7 times every night while sleeping. The instrument used as a measure of sleep quality is by using the PSQI (Pittsburgh Sleep Quality Index). Result: there is an increase in the quality of sleep by pregnant women as evidenced by a decrease in the PSQI score from 9 to 6.